2017
DOI: 10.1002/adfm.201701388
|View full text |Cite
|
Sign up to set email alerts
|

High‐Yield Synthesis of Multifunctional Tellurium Nanorods to Achieve Simultaneous Chemo‐Photothermal Combination Cancer Therapy

Abstract: Tellurium (Te) is an important semiconductor material with low band‐gap energy, which has attracted considerable attention in recent years, due to its special chemical and physical properties and wide potential in electrochemistry, optoelectronics, and biological fields. This study demonstrates a facile and high‐yield synthesis strategy of Te nanorods (PTW‐TeNRs) decorated by polysaccharide–protein complex, which can achieve simultaneous chemo‐photothermal combination therapy against cancers. PTW‐TeNRs alone p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 50 publications
3
62
0
Order By: Relevance
“…Interestingly, studies also found that, PEG or liposomes decoration of nanomaterials exhibited higher accelerated clearance during blood circulation 8b,9. Therefore, in most preclinical studies, photothermal agents have been administered via intratumoral injection to avoid the dissatisfactory hemocompatibility and blood clearance . Hence, it is urgent to find ways to improve the hemocompatibility of photothermal agents, and to enhance their blood circulation.…”
Section: Introductionmentioning
confidence: 97%
“…Interestingly, studies also found that, PEG or liposomes decoration of nanomaterials exhibited higher accelerated clearance during blood circulation 8b,9. Therefore, in most preclinical studies, photothermal agents have been administered via intratumoral injection to avoid the dissatisfactory hemocompatibility and blood clearance . Hence, it is urgent to find ways to improve the hemocompatibility of photothermal agents, and to enhance their blood circulation.…”
Section: Introductionmentioning
confidence: 97%
“…The research work shows its wider application in electronics, optoelectronics, and biomedicine field . The photothermal effect of Te nanomaterials is also found and has been utilized for photothermal cancer therapy . The bandgap of Te is only 0.35 eV, which endows a broadband absorption and efficient photothermal conversion .…”
Section: Photothermal Evaporationmentioning
confidence: 97%
“…[206][207][208][209] The photothermal effect of Te nanomaterials is also found and has been utilized for photothermal cancer therapy. [210,211] The bandgap of Te is only 0.35 eV, which endows a broadband absorption and efficient photothermal conversion. [210] Moreover, its stable photothermal performance can also be observed.…”
Section: Tellurenementioning
confidence: 99%
See 1 more Smart Citation
“…Based on published reports, TeNRs have attracted significant interest for biomedical applications owing to their low cytotoxicity and excellent photothermal conversion efficiency. [36][37][38] However, the poor colloidal stability of TeNRs during long-term storage and in physiological media have presented obstacles that prevent their substitution for conventional noble metal nanomaterials. [39][40][41] In addition to the development of a simple and attractive synthesis method using the heterogeneous precursor platform, the BTCNs overcame the limitations of TeNRs.…”
Section: Introductionmentioning
confidence: 99%